The Risks and Opportunities of the Sharing Economy Guest Editorial. (April 2016) - Ranchordás, Sofia
Abstract : In July 2014 I took my first Uber-ride in Washington, DC. Surely, I had heard earlier about the smartphone application that provided rides to local destinations in someone's private car, but the thought of stepping into a stranger's car without a taximeter and without any certification issued by a public authority was daunting. The low fares and convenience were nonetheless irresistible. At the time a number of questions arose in my mind: Are these rides safe? How does Uber control the identity of drivers? Are the risks that I incur worth the convenience and the lower price of this transaction? Is it fair to allowUber drivers to compete on the market without complying with the same requirements applicable to taxi drivers? As the protests against Uber increased, I found myself questioning whether Uber and other sharing-economy platforms were examples of a more informal economy in a positive or a negative sense. In other words, someone must be paying for the low prices, the labor flexibility, and the on-demand transactions offered by sharing-economy platforms.